Influence of Alkali Metal Cations on the Hydrogen Evolution Reaction Activity of Pt, Ir, Au, and Ag Electrodes in Alkaline Electrolytes. Issue 17 (19th June 2018) - Xue, Song; Garlyyev, Batyr; Watzele, Sebastian; Liang, Yunchang; Fichtner, Johannes; Pohl, Marcus D.; Bandarenka, Aliaksandr S.
Abstract: Fundamental understanding of the influence of so‐called spectator electrolyte species on the catalytic activity of electrodes is considered as a relatively novel direction in electrocatalysis. Numerous recent examples show that seemingly inert electrolyte components drastically influence the performance of catalytic centers. Even alkali metal cations in aqueous electrolytes at high pH values can change the reaction turnover frequency by orders of magnitude, depending on their nature, from Li + to Cs + . Here, we use several electrodes, namely Pt(polycrystalline), Pt(111), Pt(221), Ir(111), Au(111), and Ag(polycrystalline), in different alkali metal cation‐containing electrolytes to reveal their role in the hydrogen evolution reaction (HER). The HER activity trends of various Pt electrodes, irrespective of their surface structure, correlate with the hydration energy of the corresponding alkali metal cations present in the electrolyte (Li + >Na + >K + >Rb + >Cs + ). The trend remains the same for the Ir(111), however, it is reversed for Au(111) and Ag(pc) electrocatalysts. Abstract : It′s up to HER : By measuring the hydrogen evolution reaction activities of single‐crystalline Pt(111), Pt(221), Ir(111), Au(111), and polycrystalline Pt, Ag in different alkaline electrolytes, it is found that, for all Pt and Ir(111) electrodes, the activities decrease in the following order: LiOH>NaOH>KOH>RbOH>CsOH, whereas for Au and Ag electrodes, the order is reversed: CsOH>RbOH>KOH>NaOH>LiOH.